Risk factors of early proximal gastric carcinoma in Chinese diagnosed using WHO criteria. Issue 6 (June 2015) - Fang, Cheng; Huang, Qin; Lu, Lin; Shi, Jiong; Sun, Qi; Xu, Gui Fang; Gold, Jason; Mashimo, Hiroshi; Zou, Xiao Ping
<x xml:space="preserve">Abstract</x> Objective The incidence of proximal gastric carcinoma (PGC) is rising worldwide for unknown reasons. Herein we compare the risk factors of early PGC with distal gastric carcinoma (DGC) in patients treated at a single tertiary hospital in China. Methods Risk factors of 379 consecutive surgically resected early gastric carcinoma (EGC) diagnosed according to the 2010 World Health Organization criteria were studied by reviewing their medical records and esophagogastroduodenoscopy/biopsy findings and interviewing patients and family members for the patients' history of environmental toxin exposure (ETE), dietary habits, family (FCH) and personal cancer history (PCH) and survival. Differences between PGC (n = 115), DGC (n = 264) and age‐matched and gender‐matched controls (n = 225) were compared. Results Proportion of early PGC in all EGC patients was increased significantly (P < 0.05). The independent risk factors for both PGC and DGC identified by multivariate analysis were intake of preserved food and little fruit, and gastric mucosal intestinal metaplasia and atrophy (all P < 0.05). Advanced age (odds ratio [OR] 9.83, P < 0.01), PCH (OR 5.09, P < 0.05), a high body mass index (>24 kg/m2) (OR 2.79, P < 0.01) and ETE (OR 2.31, P < 0.05) were independent risk factors for PGC, but not male gender, tobacco or alcohol abuse, hiatus hernia, gastroesophageal reflux disease or columnar‐lined esophagus. In contrast, FCH (OR 2.34, P < 0.01) and Helicobacter pylori infection (OR 2.81, P < 0.001) were independent risk factors for DGC. Conclusion Independent risk factors for PGC in Chinese patients differ from those of DGC or esophageal adenocarcinoma, supporting the classification of PGC as a separate gastric carcinoma entity in the Chinese populations.